The Influence of Recruitment, Job Training and Compensation on Employee Performance at CV. Bina Reka Lamongan - Nur Fitriani; M. Sihab Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses the influence of recruitment, job training and compensation on employee performance at CV. Bina Reka Lamongan. This research uses quantitative methods. Sampling was carried out using a saturated sampling technique with a total of 70 CV employees as respondents. Bina Reka Lamongan The method in this research uses a validity test, reliability test and classic assumption test, data analysis is carried out using Multiple Linear Regression Analysis and Determination Coefficient Analysis (R²), while the hypothesis testing technique uses the t test and F test. The results of the t test research are carried out partially shows that the Recruitment variable has a positive and significant effect on employee performance, the Job Training variable has an effect but is not significant on employee performance, the Compensation variable has an effect but is not significant on employee performance. Regarding the F test, it shows that the variables Recruitment, Job Training and Compensation have a significant effect simultaneously on employee performance at CV. Bina Reka Lamongan.